Role Difficulties among Trainee Counsellors: A Conceptual Paper - Nor Mazlina, Ghazali; Lee, May Fen,; Wan Marzuki, Wan Jaafar; Azzahrah, Anuar; Edris, Aden (2018)
Role difficulties are included role conflict and role ambiguity. Clarification on role difficulties is important in ensuring the effectiveness of supervision process. The definition of role conflict is defined as the expectations of behaviour that are competing or opposing (Biddle, 1979) and role ambiguity happened when the expectations within it is incomplete and unclear to facilitate behaviour causing uncertainty (Biddle, 1979). Hence, the Role Theory mainly focus on the study of behaviour that are characteristics of a person within context and with varies processes that presumably produce, explain or are affected by those behaviour. Understanding and exploring on role difficulties it might contributed toward clear social position between trainee counsellors and supervisor, crystallised the expectations between them, identify the consequences and functions of trainee counsellors and supervisor as well as taught role to trainee counsellors. As conclusion, the clarification of role difficulties between trainee counsellors can develop the effectiveness of supervision process